Development of Pilgrimage Tourism in Uzbekistan - Obidjon Qizi, Najmiddinova Gulnora (European Journal of Life Safety and Stability (2660-9630), 2022)
The article shows the main directions of the development of pilgrimage tourism in Uzbekistan, the factors affecting it and opportunities. Also, religious tourism and its structure, definitions given by different authors to concepts such as religious structure, pilgrimage tourism, and Islamic tourism are analyzed. The progress achieved in the development of pilgrimage tourism in the country is analyzed and the tasks to be solved are highlighted.